The Programme for International Student Assessment Research in Indonesia - Musafir Rastuti; Rully Charitas Indra Prahmana (Jurnal Elemen, 2021)
Several Programme for International Student Assessment (PISA) research articles published in Indonesia have contributed to PISA research development in Indonesia, with mathematics as one of the PISA domains. However, there is no research to categorize the PISA research article to give future PISA researchers essential information. Therefore, this study aims to organize PISA research in Indonesia in the period 2016-2020. This study uses the Systematic Literature Review (SLR). The SLR method identifies, analyzes, evaluates, and categorizes specific topics related to PISA research in Indonesia. The research data comes from 27 articles published in thirteen accredited journals in the Sinta 1 and Sinta 2 category by the Ministry of Research, Technology and Higher Education of the Republic of Indonesia as an achievement for review journals, which have excellent management and publication quality. The findings indicated that nine categories were identified in this study, including the PISA articles dominance, the development of PISA model math problems, PISA research and subjects, the research methods, the content and context, students' abilities, and the level of the questions. Lastly, this research contribution also is intended to guide future PISA researchers in determining PISA research trends and the following PISA research opportunities in Indonesia.